Dehydrogenation of Formic Acid Catalyzed by a Ruthenium Complex with an N,N′‑Diimine Ligand - Guan, Chao; Zhang, Dan-Dan; Pan, Yupeng; Iguchi, Masayuki; Ajitha, Manjaly J; Hu, Jinsong; Li, Huaifeng; Yao, Changguang; Huang, Mei-Hui; Min, Shixiong; Zheng, Junrong; Himeda, Yuichiro; et al. (Inorganic chemistry, 2017)
We report a ruthenium complex containing an N,N′-diimine ligand for the selective decomposition of formic acid to H2 and CO2 in water in the absence of any organic additives. A turnover frequency of 12 000 h–1 and a turnover number of 350 000 at 90 °C were achieved in the HCOOH/HCOONa aqueous solution. Efficient production of high-pressure H2 and CO2 (24.0 MPa (3480 psi)) was achieved through the decomposition of formic acid with no formation of CO. Mechanistic studies by NMR and DFT calculations indicate that there may be two competitive pathways for the key hydride transfer rate-determining step in the catalytic process.